Corporate Currency Hedging and Currency Crises - Andreas Röthig; Willi Semmler; Peter Flaschel (Technische Universität Darmstadt, Department of Law and Economics, 2005)
We examine the impact of corporate currency hedging on economic stability by introducing hedging activity in a Mundell-Fleming-Tobin framework for analyzing currency and financial crises. The ratio between hedged and unhedged firms is modelled depending on firm size as well as hedging costs. The results indicate that, with an increasing fraction of hedged firms in an economy, the magnitude of a crisis decreases and from a specific hedging level onwards currency crises are ruled out. In order to improve corporate risk management access to hedging instruments should be made possible and hedging costs should be reduced.
Keywords: F31; E44; E32; F41; 330; Mundell-Fleming-Tobin model; currency crises; currency hedging; hedging costs; Währungsmanagement; Hedging; Währungskrise; Finanzmarktkrise; Mundell-Fleming-Modell; Theorie